KAUSALITAS PAD DAN BELANJA MODAL TERHADAP DEFISIT APBD (STUDI KASUS PROVINSI 3 JAWA PERIODE 2012-2021) - Putra, Dendy Pramana; Efendi, Lukman; Sofwan, Adiwidya Muhammad (Among Makarti, 2025)
Abstract : This study aims to know the extent to which original local government revenue and capital expenditure are related to the local government budget deficit for the 2012-2021 period. Data used is panel data with 10 years series (2012-2021) and cross-section in 3 Java Provinces (West Java, Central Java, East Java). The method used a panel data regression Common Effects Model (CEM) with help from views 9.0 software. The result of this study showed the original local government revenue that has positive influence and significant on the local government budget deficit with tcalculated the value of original local government revenue is 4.968535 and Prob. 0.0000. Meanwhile, capital expenditures are influentially negative and significant to the local government budget deficit with tcalculated value of capital expenditure is -2.069669 and Prob is 0.0482. The original local government revenue and capital expenditures simultaneously influentially significant to the local government budget deficit with mark Prob (F-Statistic) of 0.000156. Original local government revenue and capital expenditure variables predicted the deficit of local government budget deficit in 43.9%. It means variation of this variable in determines local government budget deficit is strong sufficient.Abstrak : Penelitian ini dilakukan untuk mengetahui sejauh mana Pendapatan Asli Daerah (PAD) dan belanja modal terhadap defisit APBD Periode 2012-2021. Data yang digunakan adalah data panel dengan time series 10 tahun (2012-2021) dan cross section di Provinsi 3 Jawa (Jawa Barat, Jawa Tengah, Jawa Timur). Metode yang digunakan ialah metode regresi data panel menggunakan Common Effect Model (CEM) dengan bantuan software Eviews 9.0. Hasil dari penelitian ini menunjukkan bahwa PAD berpengaruh positif dan signifikan terhadap Defisit APBD dengan nilai thitung PAD sebesar 4,968535 dan nilai Prob. 0,0000. Sedangkan Belanja Modal berpengaruh negatif dan signifikan terhadap Defisit APBD dengan nilai thitung Belanja modal sebesar -2,069669 dan nilai Prob. 0,0482. PAD dan Belanja Modal secara simultan berpengaruh dan signifikan terhadap Defisit APBD dengan nilai Prob (F-Statistic) sebesar 0,000156. Variabel PAD dan Belanja Modal dapat memprediksi Defisit APBD sebesar 43,9% yang berarti variasi variabel ini dalam menentukan defisit APBD cukup kuat.